Activity of ceftolozane-tazobactam, ceftazidime-avibactam, meropenem-vaborbactam, cefiderocol and comparators against Gram-negative organisms causing bloodstream infections in Northern Italy (2019–2021): emergence of complex resistance phenotypes. (4th July 2022) - Bianco, Gabriele; Boattini, Matteo; Comini, Sara; Iannaccone, Marco; Casale, Roberto; Allizond, Valeria; Barbui, Anna Maria; Banche, Giuliana; Cavallo, Rossana; Costa, Cristina
Abstract: Herein we assessed the frequency of Gram-negative organisms causing bloodstream infections and activity spectrum of ceftolozane-tazobactam (CTZ), ceftazidime-avibactam (CZA), meropenem-vaborbactam (MEV), cefiderocol (CFDC) and comparators. Overall, 1605 Gram-negative isolates were consecutively collected during 2019–2021. Enterobacterales represented more than 75% and exhibited >90% susceptibility to CZA (97%), amikacin (91.8%) and meropenem (90.6%). ESBL-producing Enterobacterales isolates showed high rates of susceptibility towards CZA (100%), carbapenems (89.1–100%) and CTZ (84.9–95.1%). MEV displayed the highest activity against KPC-producing Enterobacterales (MIC50/90, 0.75/4 mg/L; 92.9% susceptible) followed by CZA (MIC50/90, ≤2/>8 mg/L; 89.3% susceptible), CFDC (MIC50/90, 0.25/4 mg/L, 87.5% susceptible) and colistin (MIC50/90, ≤2/4 mg/L, 83.9% susceptible). High proportions of P. aeruginosa isolates were susceptible to colistin (97.8%), CZA (97.2%), CTZ (96.1%) and amikacin (94.5%). CFDC showed potent activity against Acinetobacter baumannii (MIC50/90, 0.5/1 mg/L; 97.2% susceptible), multi-drug resistant P. aeruginosa (MIC50/90, 0.25/1 mg/L; 96% susceptible), and Stenotrophomonas maltophilia (MIC50/90, 0.12/0.25 mg/L; 100% susceptible).